DARGENT, Eduardo, 2014, Technocracy and Democracy in Latin America: The Experts Running Government, Nueva York, Cambridge University Press. 216 pp. - Hershberg, Eric (2015)
Se reseñó el libro: Technocracy and Democracy in Latin America: The Experts Running Government.